Disability rights legislation in Nepal: Status, challenges, and way forward - Oli, Kamala (Nepal Public Policy Review, 2025)
Legislation concerning the rights of persons with disabilities encompasses legal instruments aimed at safeguarding their rights and interests, ensuring equal participation and inclusion in societal affairs. This paper investigates the landscape of rights legislation provided for persons with disabilities in Nepal, where disability issues are analyzed within social and legal discourse frameworks. Utilizing the content analysis method, this article synthesizes qualitative aspects of legal frameworks, policy documents, and existing scholarly literature with insights gleaned from secondary sources. Key concepts under scrutiny include government attention to disability rights initiatives and international obligations, the degree of legal adherence, and the accessibility of services for persons with disabilities. The research findings highlight notable legislative efforts made by the government to safeguard the rights of persons with disabilities; however, their effectiveness relies on enforcing legislation, strengthening public institutions, and encouraging contributions from non-governmental organizations. Implementing such legal frameworks was found to be weak for several reasons, including infrastructural deficiencies, lack of accurate statistical information, and inadequate policy and structural interventions at the sub-national level. Media review revealed various barriers to accessibility, education, employment, health services, social inclusion, and legislation, while also acknowledging some benefits received by persons with disabilities in education, employment, institutionalization, social protection, and resilience. Recommendations arising from this inquiry advocate for bolstered enforcement mechanisms, resource allocation, increased public awareness efforts, improved accessibility standards, and empowerment of diverse stakeholders. This research is significant given the urgent need to address the ongoing challenges in effectively implementing rights for persons with disabilities in Nepal.